The study of seat vibration transmission of a high-speed train based on an improved MISO method. (September 2020) - Wu, Jun; Qiu, Yi
Highlights: Calculating partial coherence independently of sequences of the inputs. Accelerations on seat pan and backrest are related to accelerations on floor. Peaks caused by seat modes reduced by damping from neighbouring subject. Abstract: The field measurement was carried out on a high-speed train for the vibration transmission of the seat. The transmissibilities and coherences from the accelerations at the seat base to those on the seat pan and backrest were studied by an improved multi-input and single-output (MISO) system newly proposed by the authors. The improved method has the advantage of calculating the partial coherence independently of the sequences of the inputs and evaluating the contribution of the coherent parts between the inputs to the output compared with the existing method. It was found that although the high-speed train seat was exposed to complex vibrations from different sources, when the three inputs (vertical, lateral and roll accelerations) at the seat base were used as the inputs for MISO models, good multiple coherence functions could be obtained when studying the seat transmissibility to the vertical, lateral or roll vibration at the seat pan and backrest except in the frequency range where the anti-resonances of the inputs located. In such an exceptional case, the unsatisfactory multiple coherence could be explained by the anti-resonances of the input signals, which was further verified by the laboratory experiment. Then the on-site measurement was compared with the laboratory measurement in terms of the estimation of the coherence and transmissibility. Due to the advantages of the laboratory experiment, the contribution from the coherent parts is smaller, and the multiple coherence is higher than the field measurement. In the field measurement, that the inputs were coherent with the 'noise' was the main reason for the erroneous estimation of frequency response function (FRF), but the erroneous estimation of FRF resulting from the coherence between the inputs can to some degree be figured out by adopting MISO system. Finally, it was found the peaks in the seat transmissibilities caused by seat modes usually got reduced by the neighboring subject because of the damping brought from the subject.